1972
DOI: 10.1017/s0021853700000244
|View full text |Cite
|
Sign up to set email alerts
|

Archaeology in Benin

Abstract: Excavations and fieldwork in and around Benin City in the years 1961–4 have established the outlines of an archaeological sequence. This sequence is based on radiocarbon dates for stratified deposits, on a statistical examination of pottery form and decoration, and on datable European imports. The sequence suggested by the evidence extends from about the thirteenth century A.D. to the present time, although the survival of locally found ground stone axes in Benin ritual indicates that the area may well have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Historical evidence have shown that the Portuguese agent, Afonso d' Aveiro visited Benin kingdom in 1485 during the reign of Oba Ozoula, and established commercial and diplomatic relations between both countries. Aveiro returned to Lisbon with the Chief of Ughoton, who acted as the Obas's Ambassador (Connah, 1972) which eventually led to the establishment of a trading factory by the Chief of Ughoton. Subsequent interactions between Portugal and Benin kingdom continued even up to the reign of Oba Esigie who later was converted to a Christian by the missionaries.…”
Section: Benin Contact With the Europeanmentioning
confidence: 99%
“…Historical evidence have shown that the Portuguese agent, Afonso d' Aveiro visited Benin kingdom in 1485 during the reign of Oba Ozoula, and established commercial and diplomatic relations between both countries. Aveiro returned to Lisbon with the Chief of Ughoton, who acted as the Obas's Ambassador (Connah, 1972) which eventually led to the establishment of a trading factory by the Chief of Ughoton. Subsequent interactions between Portugal and Benin kingdom continued even up to the reign of Oba Esigie who later was converted to a Christian by the missionaries.…”
Section: Benin Contact With the Europeanmentioning
confidence: 99%
“…However, from what is left of the physical characteristics of settlement walls, it might be possible to determine why the wall was constructed in the first place. Several studies have referred to enclosing walls as defensive features (Connah, 1972;Haase, 1985;Lafferty, 1973;Okpoko, 1987;Ozanne, 1969;Webster, 1975). Apparently the encircling nature of some walls (whether partial or complete), the height and width, and the number and type of entry gates, were sufficient reason to call them defensive.…”
Section: Functional Interpretationmentioning
confidence: 99%
“…While there are no data from Igbomina to test the sequence of walls development, what is known from dated charcoal is that construction of walls and ditches may have followed the large-scale immigration into Igbominaland in the 16th century. Elsewhere in Africa attempts to address such issue have been very successful (Connah, 1975;Ozanne, 1969;Quarcoopome, 1993;Soper and Darling, 1980;Sutton, 1976). The archaeological study of the remains of the Kano city wall by Moody, for example, identified three phases of growth in the wall system: in the 11th and 12th century AD, the late 15th century, and the 17th century; a sequence documenting the growing size and importance of the city as the second millennium AD progressed (Moody, 1967).…”
Section: Functional Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Although ditch systems (or, more frequently, wall and ditch complexes) are known for other West African towns, such as Nots6 and Tinipe in Togo (Aguigah, 1989;Kuevi, 1989;Posnansky, 1981Posnansky, , 1985Quarcoopome, 1993), K6tou and Abomey in B6nin (Gayibor, 1985), and Ipapo Ile and Benin City in Nigeria (AgbajeWilliams, 1989(AgbajeWilliams, , 1990Connah, 1975), these wall systems generally enclose entire towns, and are not limited to the elite district. In addition to a symbolic role in defining town space, the continuous nature of these ditches outside the towns suggest that some, if not all, might have been built for defensive purposes.…”
Section: Archaeological Evidencementioning
confidence: 99%